Successful Management of Giant Placental Chorangioma by Microcoil Embolization - Stephen P. Emery; Philip D. Orons; Jeffrey F. Bonadio (Thieme Medical Publishers, Inc., 2018)
Optimal prenatal management of giant placental chorangioma (also known as chorioangioma, angiomyxoma, fibroangiomyxoma, or fibroma) has yet to be determined. Interventions intended to devascularize the tumor such as interstitial laser, bipolar coagulation, fetoscopic laser photocoagulation, and chemical embolization have met mixed results. We report a minimally invasive, extra-amniotic approach, technically similar to cordocentesis, of microcoil embolization of the feeding vessel. These percutaneously placed microcoils initiate clot formation at the site of insertion and are unable to migrate through the tumor, thereby minimizing fetal harm by downstream embolic phenomena. Intervention at 26 and 22 weeks resulted in intraoperative fetal loss in the former and vaginal delivery at term of a healthy neonate in the latter. Preoperative, intraoperative, and placental findings are highlighted. The ease and safety of this procedure may alter the risk-benefit equation toward earlier intervention with potentially better clinical outcomes.